Semiology therapy and analgesia in acupuncture - Nguyễn Tài Thu (Thế Giới, 1998)
This book should be as a concise handbook on acupuncture for it offers a wide range of knowledge of the traditional diagnosis and clinical application of acupoints, acupuncturing techniques, analgesic acupuncture, and others